Processos de ensino-aprendizagem para prevenção do HIV/AIDS: possibilidade para a mudança comportamental de mulheres - Santos, Luiz Eduardo dos [UNIFESP] (2014)
The feminization of the epidemic is one of the current challenges preventing AIDS. The current prevention policies are not reducing the growth of the epidemic in this segment. This study investigated the process of teaching and learning about AIDS prevention and the apprehension of this knowledge for the possible change in attitudes of adult women assisted by Joan of Arc Institute. Research explanatory character, uses a qualitative approach, developed in four groups of family and community empowerment led by Joan of Arc Institute in the city of Bertioga, São Paulo, through a strategy called ?round of conversation? from March/2013 until February/2014. The study involved the following steps: observation in loco of 14 ?round of conversation? Wheels of Conversation developed in Bertioga Reference Centres for Social Assistance, São Paulo; interview with a professional body responsible for the implementation of the contents in the community; the application of a questionnaire for the inclusion or non-inclusion with women groups of respondents; conduct two semi-structured interviews with selected women. The goal was to understand the social and gender relations, their perception of HIV risk and the possibility of being vulnerable to AIDS. 65 questionnaires were administered to women aged between 18 and 60 years and, after the inclusion criterion for the search resulted in 22 women for the first interview, seven in group 1; four in group 2; eight in group 3 and three in group 4 In the second study, nine women were interviewed four of the group 1; one of the group 2; two of the group 3; two of the group 4. The interviews took place in two specific times in July and August/2013 and in January and February/2014, in order to analyze the results obtained in both cases, the existence of similarities or differences in absorption of information, the acquisition of new knowledge and if there is effectiveness in the teaching-learning model applied by the entity as a way to assist in developing preventive strategies that facilitate the apprehension of knowledge about AIDS, by reducing the risk of HIV infection and other STDs. For the content analysis, we use the proposed Bardin. For the groups studied, there are a difficulty in the perception of risk to HIV in their sexual-affective relationships by not recognizing its possibility of infection. The results show that women recognize the modes of transmission, prevention and protection, the main sexually transmitted diseases and that there is an evolution of knowledge between periods of interviews. However, there is no apprehension of knowledge and its practical application in their daily lives. The factors that hinder the assimilation of content are affective and desire relationships - trust, social roles and gender relations; taboos concerning sexuality; low knowledge of health education, resulting in how individuals interpret and absorb these differences. The efforts of the organization to reduce this problem are on track, with the application of ?round of conversation? as a teaching-learning strategy in health, but there is a definite methodological project to organize the actions to be applied next to this population segment. The results demonstrate the necessity of creating an Institutional Political Pedagogical Project setting, the methodological process of health education, information related to AIDS and that include all the cultural, educational and social diversity of women, drawing a parallel between sexual health and reproductive, the AIDS epidemic and gender relations. For its implementation, should consider, in addition to prior knowledge of each individual, partners or extended to the male population of their social context, different ways of learning through the exchange of experiences, stories of life and enabling informed choices preventive means according to their way of life.